Does the use of differentiated instruction through project-based learning in mathematics classroom settings facilitate the students’ collaborative skills? - Andriyani, Zuni Dwi; Wijayanti, Dyana; Ubaidah, Nila; Lutfi, Ahmad; Meng, Danyang (Jurnal Elemen, 2024)
This research aims to describe differentiated instruction through project-based learning on students' collaborative skills in solid geometry.  This study is a case study type of research. Data collection techniques were carried out by observing and interviewing 32 students. The result of this research is that differentiated instruction begins with an assessment of student readiness and an assessment of student interest. The learning process continues with implementing three essential aspects of differentiated instruction: content, process, and product differentiation. Process differentiation begins with the implementation of project-based learning steps. In this case, differentiated teaching and project-based learning complement each other. The results of the collaborative skills show that the students in the forming category performed optimally. Pupils learn in groups voluntarily; pupils do not leave their groups, and they exchange ideas when completing their projects. However, in the other categories, i.e., students' functioning, formulating, and fermenting, they do not show maximum results.